Perbedaan Pengetahuan, Sikap dan Praktik Keselamatan dan Kesehatan Kerja Laboratorium antara Mahasiswa Program Studi D3 dan S1 pada Institusi Pendidikan di Semarang - Priska Ruth Dantje; Baju Widjasena; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Occupational safety and health is one of the most important issues in globalization era including in academic institution which contributes for improving science and technology. Chemical laboratory at educational institution is part of learning process. Chemical laboratory is a place where both undergraduate diploma and undergraduate bachelor student enhancing their competence yet it has high risk of potential danger for everyone who practice in laboratory. Some chemistry classes in lab such as organic chemistry and analytical chemistry is compulsory for undergraduate diploma and undergraduate bachelor student. However, occupational safety and health class is only for undergraduate diploma student. Thus, the purpose of this study is to determine the difference of knowledge, attitude and practice toward laboratory safety between undergraduate diploma and undergraduate bachelor students at educational institution. This research is quantitative and qualitative study using comparative method. The independent variable is the availability of occupational safety and health class while dependent variable consists of knowledge, attitude and practice toward lab safety. Using independent t-test and Mann Whitney test show that there is no difference of knowledge, attitude and practice toward lab safety between undergraduate diploma and undergraduate bachelor students. The recommendation which given are continuously occupational safety and health class for all undergraduate students and safety awareness training for lecturer and lab staff at educational institution in Semarang.